2021
DOI: 10.21829/myb.2021.2722047
|View full text |Cite
|
Sign up to set email alerts
|

Performance of mycelium composites of Lentinus crinitus under two compression protocols

Abstract: Considering the current environmental problems that has been generated by the excessive production of synthetic plastics, more sustainable alternatives have been proposed. One of these recently studied materials are the mycelium composites, a product obtained with lignocellulosic particles agglomerated together by the myceliar growth of a filamentous fungus. This novel type of materials could represent an option to replace non-biodegradable materials. In this work, mycelium composites with characteristics comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the latter figure we can notice the increased mechanical efficiency of the BM_R series thanks to the composition strategy. In both figures flexural reports from the published MBC state-of-the-art are plotted [ 3 , 4 , 5 , 11 , 12 , 18 , 19 , 20 , 21 , 22 ]. These two figures gather evidences produced with approximately ten fungal species, two studies having not disclosed the ones they used [ 5 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter figure we can notice the increased mechanical efficiency of the BM_R series thanks to the composition strategy. In both figures flexural reports from the published MBC state-of-the-art are plotted [ 3 , 4 , 5 , 11 , 12 , 18 , 19 , 20 , 21 , 22 ]. These two figures gather evidences produced with approximately ten fungal species, two studies having not disclosed the ones they used [ 5 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Densified specimens have been reportedly leading to an increase of flexural modulus between 27 and 72-fold, and 4 to 14.5-fold increase in flexural strength for a densification from 100–130 kg/m 3 to 350–390 kg/m 3 [ 3 ]. While staying at the lower end of MBC densities, another study reported an increase of 4.4-fold in flexural strength while increasing composite density by a factor 1.4 (from 102 to 141 kg/m 3 ) [ 4 ]. Composition is a second strategy for modifying MBC behaviour by adding structural components to the substrate, including, for instance, orientated fibres or textiles.…”
Section: Introductionmentioning
confidence: 99%
“…9 ). In both figures compressive characterisation from the published MBC state-of-the-art are plotted 4 7 , 35 43 . These figures gather evidences produced with approximately ten fungal species, two studies having not disclosed the ones they used 6 , 36 .…”
Section: Compressive Behaviourmentioning
confidence: 99%